Kajian Hukum Praktik Pengobatan Tradisional Berbasis Metafisik dalam Perspektif Regulasi UU Nomor 1 Tahun 2023 dan UU Nomor 17 Tahun 2023 - Gabriella Naipospos (Jurnal Hukum Caraka Justitia, 2025)
Traditional metaphysical-based healing practices are an integral part of Indonesian culture, particularly in rural areas where access to modern healthcare services remains limited. Although not always supported by empirical medical evidence, the public’s trust in these time-honored methods and their spiritual values keeps these practices relevant. However, national regulatory dynamics have raised new issues, particularly following the enactment of Law Number 17 of 2023 on Health, which recognizes traditional medicine as part of the national health system, and Law Number 1 of 2023 on the Criminal Code, which introduces criminal penalties for non-medical practices deemed harmful or misleading. This regulatory duality creates legal uncertainty and dilemmas for traditional healers in obtaining legal recognition and protection. This study aims to analyze the conflict of norms between the two laws in the context of the legitimacy of metaphysical-based traditional medicine and provide recommendations for regulatory harmonization. The research method used is normative law with a legislative and conceptual approach, supported by a literature review of primary and secondary legal materials. The results of the study indicate that regulatory disharmony has resulted in limited legal protection for traditional healers, while service users are in a vulnerable position due to the absence of adequate supervision and protection.